Diagnosing Primary Pupils Learning of the Concept of After in The Topic Time Through Knowledge States by Using Cognitive Diagnostic Assessment - Tan, Phei Ling; Lim, Chap Sam; Kor, Liew Kee (Universiti Utara Malaysia Press, 2017)
Purpose - Knowledge state specifies pupils mastery level and informs about their strength and weaknesses in the tested domain. This study attempted to diagnose primary pupils learning the concept of after through their knowledge states by using Cognitive Diagnostic Assessment (CDA).